The Function of Association as A Community Empowerment Process in Independent Food Village Program ( DEMAPAN ) - Faqih, Achmad (International Journal of Psychosocial Rehabilitation, 2020)
Counseling function is to bridge the gap between the practices that are usually carried out by the target ( farmers ) with the knowledge and technology that always develops into the needs of the target. The counseling function is referred to as a link that outlines the process of delivering science and technology from its source to the people who need it. The function of the counseling system includes: facilitating the learning process, easy access, improving leadership abilities, developing the organization, analyzing and solving problems. Community empowerment is the concept of economic development that encapsulates the values of society to build a new paradigm in people-centered, participatory, empowerment and sustainable development. This research was conducted in Tegalsari Village, Plered District, Cirebon Regency. Held from July 2018 to January 2019, the aim was to find out the counseling function of the community empowerment process in the DEMAPAN program with a sample of 60 farmers. The method research that used in this research is descriptive and quantitative research, which aims to describe the symptoms that occur during the study. The researched variable include the counseling function variable and the community empowerment process in the DEMAPAN program activities. To find out the researched variable, descriptive data analysis was used with primary and secondary data, multiple linear regression analysis, and the F test and the t-test (two different test average paired samples). The results showed that the counseling function variable had a significant effect on the process of community empowerment in the DEMAPAN program, as evidenced from the results of the analysis obtained a value of Tcount of 7.492> Ftable 4.013, with a significance value of 0.002 <0.005. This shows that the better counseling function variable of the five indicators is learning process facilities, easy access, improving leadership skills, developing organizations, analyzing and solving problems will be followed by increasing community empowerment in the DEMAPAN program.